Nutritional niches reveal fundamental domestication trade-offs in fungus-farming ants - Shik, Jonathan Z.; Kooij, Pepijn W. [UNESP]; Donoso, David A.; Santos, Juan C.; Gomez, Ernesto B.; Franco, Mariana; Crumière, Antonin J. J.; Arnan, Xavier; Howe, Jack; Wcislo, William T.; Boomsma, Jacobus J. (Springer Nature, 2021)
During crop domestication, human farmers traded greater productivity for higher crop vulnerability outside specialized cultivation conditions. We found a similar domestication trade-off across the major co-evolutionary transitions in the farming systems of attine ants. First, the fundamental nutritional niches of cultivars narrowed over ~60 million years of naturally selected domestication, and laboratory experiments showed that ant farmers representing subsequent domestication stages strictly regulate protein harvest relative to cultivar fundamental nutritional niches. Second, ants with different farming systems differed in their abilities to harvest the resources that best matched the nutritional needs of their fungal cultivars. This was assessed by quantifying realized nutritional niches from analyses of items collected from the mandibles of laden ant foragers in the field. Third, extensive field collections suggest that among-colony genetic diversity of cultivars in small-scale farms may offer population-wide resilience benefits that species with large-scale farming colonies achieve by more elaborate and demanding practices to cultivate less diverse crops. Our results underscore that naturally selected farming systems have the potential to shed light on nutritional trade-offs that shaped the course of culturally evolved human farming.